(untitled) (Academicia Globe: Inderscience Research, 2023)
In this article, we will discuss the history of the "spider web" that is the Internet (social network), which is common in our time and has a great influence on the minds of the youth of our motherland. Measures to combat it, directing the minds of young people who are addicted to the Internet to the right path, and education of today’s youth on the Internet are discussed. Also, there is a discussion about the education of the globalized age and the globalized youth.